1999
DOI: 10.1046/j.1365-2796.1999.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid treatment in patients with cholesterol gallstones: failure to detect a suppression of cholesterol
7α‐hydroxylase activity

Abstract: Abstract. Hillebrant C-G, Nyberg B, Angelin B, Axelson M, Bjo Èrkhem I, Rudling M, Einarsson C (Huddinge University Hospital and Karolinska Hospital, Karolinska Institute, Stockholm, Sweden). Deoxycholic acid treatment in patients with cholesterol gallstones: failure to detect a suppression of cholesterol 7a-hydroxylase activity. J Intern Med 1999; 246: 399±407.Objectives. Based on animal studies, hydrophobic bile acids have been postulated to be particularly strong inhibitors of bile acid synthesis. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
1
7
2
Order By: Relevance
“…This would also support evidence in humans showing a discrepancy between indices of bile acid synthesis in vivo and 7␣-hydroxylase expression and activity in vitro, as in obesity 53,54 or during deoxycholic acid treatment. 11,12,55 The finding of more pronounced suppression, or lack of increase, of bile acid synthesis in vivo compared with the determination of tissue expression of the enzyme is consistent with regulation beyond enzyme transcription and translation.…”
Section: Discussionsupporting
confidence: 56%
“…This would also support evidence in humans showing a discrepancy between indices of bile acid synthesis in vivo and 7␣-hydroxylase expression and activity in vitro, as in obesity 53,54 or during deoxycholic acid treatment. 11,12,55 The finding of more pronounced suppression, or lack of increase, of bile acid synthesis in vivo compared with the determination of tissue expression of the enzyme is consistent with regulation beyond enzyme transcription and translation.…”
Section: Discussionsupporting
confidence: 56%
“…In experimental animals, deoxycholate is a strong inhibitor of bile acid synthesis (22), compatible with a low rate of bile acid formation in some gallstone patients (23). On the other hand, the effect of deoxycholate in humans is controversial (24,25) and most studies in gallstone patients report an increase in both bile acid turnover (19,26) and synthesis (27,28). Increased biliary deoxycholate levels, bile acid turnover, and synthesis may all occur as a response to an increased ileal loss of bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Based on animal studies, it was postulated that hydrophobic bile acids are particularly strong inhibitors of bile acid synthesis (34)(35)(36). Bile acid feedback regulation in humans has also been established (37), although Hillebrant et al (38) found no effect of deoxycholic acid treatment on hepatic cholesterol 7-a-hydroxylase in patients with cholesterol gallstones. Furthermore, the fractional catabolic rates of cholic and chenodeoxycholic acid were found to be increased in gallstone carriers compared with controls (32).…”
Section: Discussionmentioning
confidence: 99%